2015
DOI: 10.1128/jb.02566-14
|View full text |Cite
|
Sign up to set email alerts
|

Ugp and PitA Participate in the Selection of PHO-Constitutive Mutants

Abstract: Mutations that cause the constitutive expression of the PHO regulon of Escherichia coli occur either in the pst operon or in the phoR gene, which encode, respectively, a high-affinity P i transport system and a histidine kinase sensor protein. These mutations are normally selected on glycerol-2-phosphate (G2P) as the carbon source in the presence of excess P i . The emergence of early PHO-constitutive mutants, which appear after growth for up to 48 h on selective medium, depends on the presence of phoA, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 43 publications
0
11
0
1
Order By: Relevance
“…PHO-constitutive mutants can be isolated by plating wild-type bacteria on glycerol-2-phosphate (G2P) as the sole C source. We have previously observed that the frequency of such mutants in bacteria carrying both Δ pitA and Δ ugp knockouts is extremely low [13]. This is because as most PHO-constitutive mutations occur in one of the five genes of the pst operon, a Δ pitA pst strain would lack a functional Pi-uptake system and will thus not be able to grow with Pi as a phosphorus source.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PHO-constitutive mutants can be isolated by plating wild-type bacteria on glycerol-2-phosphate (G2P) as the sole C source. We have previously observed that the frequency of such mutants in bacteria carrying both Δ pitA and Δ ugp knockouts is extremely low [13]. This is because as most PHO-constitutive mutations occur in one of the five genes of the pst operon, a Δ pitA pst strain would lack a functional Pi-uptake system and will thus not be able to grow with Pi as a phosphorus source.…”
Section: Resultsmentioning
confidence: 99%
“…Of the four tested transport systems, only Ugp was unable to support growth and take up Pi. In a previous study, we have shown that the emergence of PHO-constitutive mutants on plates containing glycerol-2-phosphate (G2P) as the sole carbon source partially depends on the presence of Ugp [13]. The hypotheses raised to explain this phenomenon were that Ugp was required for the uptake of either G2P or Pi.…”
Section: Discussionmentioning
confidence: 99%
“…Pst is encoded by the pstSCAB-phoU genes, or in short pst operon. Mutations in any one of the five pst operon genes result in the constitutive expression of the PHO regulon, i.e., maximal synthesis of all PHO proteins even under conditions of excess Pi [13,14]. Thus, the Pst system, besides being the principal Pi-uptake system in E. coli, also acts as a repressor of the PHO regulon [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The glycerol moieties released by AP activity thereby enter the cell mostly by facilitated diffusion via GlpF [ 18 , 19 ]. Thus, the constitutive expression of AP caused by the pst mutation enables E. coli to grow on G2P medium [ 14 , 20 ]. It should be added that some mutations in phoR also result in the constitutive expression of the PHO regulon and likewise confer the ability to grow on G2P.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation